2020
DOI: 10.1101/2020.04.22.056127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heterogeneous expression of the SARS-Coronavirus-2 receptor ACE2 in the human respiratory tract

Abstract: 15Running title: Expression of ACE2 in the human respiratory tract 16 17 Impact: The mapping of ACE2, the receptor for SARS-CoV-2, to specific anatomical regions 18 and to particular cell types in the human respiratory tract will help guide future studies and 19 provide molecular targets for antiviral therapies. We saw no increase of receptor expression in 20 the presence of known risk factors for severe coronavirus disease 2019. 21 22 Abstract: 35 Rationale: Zoonotically transmitted coronaviruses are responsi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 62 publications
(40 reference statements)
2
21
1
Order By: Relevance
“…5a). These results differ from some, but not all, recent gene expression studies comparing ACE2 expression in patients with varying demographics and smoking status [35][36][37] . Our results suggest that host factors outside of ACE2 expression may determine why males, patients of older age, and smokers are epidemiologically linked to COVID-19 susceptibility.We next examined whether ACE2 expression in the upper respiratory cilia differs between healthy donors versus patients with chronic rhinosinusitis (CRS), a non-malignant chronic .…”
contrasting
confidence: 99%
“…5a). These results differ from some, but not all, recent gene expression studies comparing ACE2 expression in patients with varying demographics and smoking status [35][36][37] . Our results suggest that host factors outside of ACE2 expression may determine why males, patients of older age, and smokers are epidemiologically linked to COVID-19 susceptibility.We next examined whether ACE2 expression in the upper respiratory cilia differs between healthy donors versus patients with chronic rhinosinusitis (CRS), a non-malignant chronic .…”
contrasting
confidence: 99%
“…Third, the number of target cells was xed to 0.1% of the total susceptible cells. This hypothesis is supported by the fact that in humans 0.1% of alveolar type II cells expressing the ACE2 receptor, gate for SARS-CoV-2 to enter host cells 17,18 . Such estimate is unknown to our knowledge in cynomolgus macaques.…”
Section: Discussionmentioning
confidence: 92%
“…Initial theories suggested that the expression level of the ACE2 receptor determined the level of disease severity in children 9 . However, more recent studies in COVID-19 patients show conflicting results and even a paradoxical increase of ACE2 in young children 4,10 . This result raises the question, What controls SARS-CoV-2 entry?…”
Section: Introductionmentioning
confidence: 96%